2009
DOI: 10.1002/dc.21216
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration biopsy as an initial diagnostic modality in a clinically unsuspected case of invasive maxillary fungal sinusitis: A case report

Abstract: Cases of invasive fungal lesions involving the paranasal sinuses are generally diagnosed either on histologic examination or on fungal culture. Here, we report a case of invasive fungal sinusitis diagnosed primarily by a fine-needle aspiration biopsy (FNAB).Our patient was a 36-year-old male who presented with a history of slowly progressive, painless swelling over the left cheek. The only positive clinical finding was a bony hard swelling in the left maxillary region, which was clinically interpreted as "fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…Vinas et al (15) detected underlying diseases including hematological malignancy, chronic granulamatosis, organ transplantation, corticosteroid use, surgical intervention history, tuberculosis in most of the patients in their study, while no immunosuppressants were reported in three patients as in our case. Fibrous dysplasia and Aspergillus infections may interfere in the clinical diagnosis (16), however in our case there was a coexistence of Aspergillus infection and fibrous dysplasia. In Aspergillus infections, spinal involvement is seldom and radiological findings remind tuberculosis (2).…”
Section: Discussionmentioning
confidence: 51%
“…Vinas et al (15) detected underlying diseases including hematological malignancy, chronic granulamatosis, organ transplantation, corticosteroid use, surgical intervention history, tuberculosis in most of the patients in their study, while no immunosuppressants were reported in three patients as in our case. Fibrous dysplasia and Aspergillus infections may interfere in the clinical diagnosis (16), however in our case there was a coexistence of Aspergillus infection and fibrous dysplasia. In Aspergillus infections, spinal involvement is seldom and radiological findings remind tuberculosis (2).…”
Section: Discussionmentioning
confidence: 51%
“…In the current series, the patients presented with mass lesions involving nose and paranasal sinuses with and without proptosis, nasal discharge and obstruction, mimicking malignancy. This has been the experience with other centres as well [1][2][3][4][5][6][7][8]. Patients may also complain of facial and dental pain, headache and decreased vision.…”
Section: Discussionmentioning
confidence: 90%
“…It can also be used for diagnosis of fungal etiology in rhino-sinusoidal inflammation. In literature there are only few case reports which describe diagnosis of rhinosinusoidal mycoses on cytology [3][4][5]. We present a series of nine such cases diagnosed on FNA.…”
Section: Introductionmentioning
confidence: 99%
“…However, utility of this approach has been limited to cases with significant sinus involvement. 16 Given the atypical presentation of our case with respect to limited sinus involvement, a surgical approach was indicated. We performed a lateral orbitotomy extending intracranially to the middle cranial fossa to directly biopsy the region without a craniotomy, minimizing surgical morbidity.…”
Section: Invasive Cavernous Sinus Aspergillosis: An Orbitocranial Appmentioning
confidence: 92%